Accumulator-based test generation for robust sequential fault testing in DSP cores in near-optimal time. - Voyiatzis, I. (IEEE Transactions on VLSI systems)
The detection of robustly detectable sequential faults has been extensively studied. A number of researchers have provided theoretical as well as experimental results designating that the application of single input change (SIC) pairs of test patterns results in favorable results for sequential fault testing. In this paper, a novel algorithm for the generation of SIC pairs is presented, termed Accumulator-based test generation for Robust sequential fault testing in Near-optimal time (ARN). ARN is implemented in hardware utilizing an accumulator whose inputs are driven by a barrel shifter. Since such structures are commonly found in general-purpose or specialized microprocessors or digital signal processors (DSP), the presented architecture provides a practical solution for the built-in testing of such circuits.